Determination of Artepillin-C in Brazilian Propolis by HPLC with Photodiode Array Detector - Yasuhito Nobushi; Naoki Oikawa; Yuzo Okazaki; Shigetoshi Tsutsumi; Yong Kun Park; Masahiko Kurokawa; Ken Yasukawa (Journal of Pharmacy and Nutrition Sciences, 2012)
A method for the determination of artepillin-C using HPLC coupled with photodiode array (PDA) detector was developed. Artepillin-C is abundantly present in Brazilian propolis of Baccharis species origin. The chromatographic separation was performed on a Mightysil RP-18 GP II column (150 mm × 4.6 mm, 5.0 ?m; Kanto Chemical Company Limited), and column temperature was maintained at 40°C. The mobile phase was a linear gradient elution of 0.5% aqueous acetic acid (A) and acetonitrile (B) at a flow rate of 1.0 ml/min. The chromatogram was monitored at 320 nm. The calibration range of artepillin-C was 0.75-2500 ?g/ml (r2 = 0.9991). The limit of detection (LOD) and limit of quantification (LOQ) were 0.50 ?g/ml and 0.75 ?g/ml, respectively. The intra-day and inter-day precision of the assay (RSD) were in the range 1.28-5.60% and 1.45-6.75%, respectively. The artepillin-C content in Brazilian propolis is an important factor in ensuring the quality of Brazilian propolisof Baccharis species origin. This method was used to determine artepillin-C content in Brazilian propolis.